CEO Capability and CEO Arrogance: Their Relationship with Fraudulent Financial Statement Indication - Magdalena, Renna; Dananjaya, Yanuar (International Journal of Scientific Research and Management (IJSRM), 2021)
This study aims to see the effect of the CEO Capabilities and CEO Arrogance to fraudulent financial statements indication. The study used a sample of all manufacturing companies from 2017 to 2019. In accordance with the sample selection, there are 162 manufacturing companies that meet the sample criteria. In this study using multiple linear regression test. This study uses secondary data for the 2017-2019 annual report.Based on the results that have been tested, CEO capability as a respected party (CEO Age), CEO capability as the person who knows the most about the company (CEO Tenure) and CEO arrogance as a person who has political connections (CEO Political Connection) have an influence on the indication of fraudulent financial statements. Furthermore, the hypothesis of CEO Capability in Accounting/finance knowledge (CEO Education), CEO arrogance in the form of narcissism (CEO PIC) and CEO arrogance as company founder (Founder CEO) have no influence on indications of fraudulent financial statements.